THE IMPLEMENTATION OF CONTEXTUAL TEACHING AND LEARNING TO IMPROVE STUDENTS’ SPEAKING SKILLS VIEWED FROM STUDNETS’ CREATIVTY - Nining Wulandari (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2016)
In MAN Ngrambe, the teaching English seems to focus on reading and listening for the sake of the national examination. Therefore, it causes the teaching of the other two English skill; writing and speaking is paid less attention. This research focuses on speaking since one of the classes the researcher teaches, a class of eleventh grade students has problem in speaking. Students are passive because they cannot speak up and have no interest in speaking practices although they are good at reading and listening. Its impact is quite obvious that in the speaking assessments the students’ scores are low. The minimum passing grade for the eleventh grade is 76 in 0 -100 scale while the researcher found out that were only 15 students (42.86 % of total students) who passed assessment on English speaking ability and only 19 students (54.29 % of the total students) who passed assessment on students’ creativity toward the teaching of speakingOne of the appropriate methods in developing speaking skill is Contextual Teaching and Learning (CTL). Johnson (2002: 205) states that CTL is an educational process that aims to help student see meaning in the academic subject with the context of their daily lives, that is, with the context of their personal, social, and cultural circumstances. To achieve this aim, the system encompasses the following eight components: making meaningful connections, doing significant work, self-regulated learning, collaborating, critical and creative thinking, nurturing the individual, reaching high standards, and using authentic assessments. It can be stated that CTL is the method that helps students relate subject matter content to real world situations and motivate students to make connections between knowledge and its applications to their lives as family members, citizens, and workers and engage them in the hard work that learning requires. In such an environment, students will discover meaningful relationship between abstract ideas and practical applications in the context of the real world. Concept is internalized through process of discovering, reinforcing and relating. Keywords: CTL, Speaking, Students’ creativity, CAR